Solar–wind hybrid renewable energy system: A review. (May 2016) - Khare, Vikas; Nema, Savita; Baredar, Prashant
Abstract: The demand for electricity is increasing day by day, which cannot be fulfilled by non-renewable energy sources alone. Renewable energy sources such as solar and wind are omnipresent and environmental friendly. The renewable emulnergy sources are emerging options to fulfill the energy demand, but unreliable due to the stochastic nature of their occurrence. Hybrid renewable energy system (HRES) combines two or more renewable energy sources like wind turbine and solar system. The objective of this paper is to present a comprehensive review of various aspects of HRES. This paper discusses prefeasibility analysis, optimum sizing, modeling, control aspects and reliability issues. The application of evolutionary technique and game theory in hybrid renewable energy is also presented in this paper.